THE ROLE OF AZOTOBACTER CHROOCOCCUM AND AZOTOBACTER PASPALI BACTERIA IN BROADCAST FERTILIZATION METHODS IN ULTISOL PLANTING MEDIA ON THE GROWTH OF PHASEOLUS RADIATUS (L.) FABACEAE. PLANTS - Sartika Pakpahan; Erwin Junaidi Lubis (Jurnal Media Akademik (JMA), 2026)
Azotobacter bacteria are a type of bacteria that can capture nitrogen from the air and convert it into nutrients that can be absorbed by plants. This process is called nitrogen fixation, which is an important nutrient in plant growth. Azotobacter chroococcum and Azotobacter paspali bacteria are very useful for soil fertility. These bacteria maintain the balance of microbes in the soil and improve the physical properties of the soil, one of which is soil structure. With the addition of these bacteria to Ultisol soil, the Ultisol soil becomes more fertile and better due to the addition of plant fertilization using the Broadcast method, and the soil will be better at storing water and nutrients in the soil for the growth of Phaseolus radiatus (L.) Fabaceae. plants. In this study, the application of Azotobacter chroococcum and Azotobacter paspali bacteria formulated with the Broadcast fertilization method at a rate of 10 g.polybag-1 was the best treatment for the growth of Phaseolus radiatus (L.) Fabaceae. plants.